Reflection the organizational Ambidexterity on organizational excellence An exploratory study at the Iraqi Cotton Industries Company - Mohammed Ali, Alia jawad (Journal of Economics and Administrative Sciences, 2020)
Organizations of various activities strive to excel and continue in light of the challenges they face, so they seek to have leaders and workers in them for the ingenuity that is reflected in their excellence in work and achievement that is achieved through the adoption of the best modern technological technologies to reach Organizations to the best levels and thus achieve their goals easily and successfully. The research aims are to know the correlation and impact between organizational proficiency and the dimensions of Organizations excellence (leadership excellence, and distinguish subordinates and excellence in organizational structure) at the Cotton Industries Company through the adoption of a unit of measurement which is the questionnaire prepared to collect data and information and to measure dimensions and analyze them by adopting the statistical program (spss) , In calculating the mean and standard deviation, then test (F) and the coefficient of determination to get the best result (60) questionnaires were distributed to administrative leaders at various levels as well as to a number of workers with experience and competence in the work and the response rate was( 100%). The research reached a number of results, including having a relationship significant correlation with statistical significance between organizational proficiency and the dimensions of Organizations excellence, and that the answers of the research sample were consistent in a large proportion, so a set of recommendations was suggested, including attention to providing competent human cadres that possess ingenuity and expertise in work at all levels as well as the development and rehabilitate those present through training courses at home and abroad to increase their capabilities and work experience in line with the latest global development.